2019
DOI: 10.1080/20008198.2019.1608719
|View full text |Cite
|
Sign up to set email alerts
|

The mediating role of posttraumatic stress reactions in the relationship between child abuse and physical health complaints in adolescence and young adulthood

Abstract: Background: Child abuse is associated with physical health problems in adolescence and adulthood, but the mechanisms involved are unclear. A possible mediating effect of posttraumatic stress reactions (PTSR) linking child abuse with later physical health complaints has not been fully investigated. Objective: The current study investigated whether PTSR could be a potential mediator in the relationship between child abuse and physical health complaints in adolescents and young adults. If so, we also investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 55 publications
1
8
0
Order By: Relevance
“…This finding was consistent with retrospective studies of adults who had experienced child abuse that showed that psychological and physical health problems co‐occurred into adulthood 3,4 . Early identification and treatment of trauma symptoms may help to reduce the daily health burden of abused adolescents, because such symptoms may already contribute to the development of physical health complaints at a young age 23 . In fact, treating trauma symptoms has been shown to be beneficial for treating physical health complaints in adults 24 …”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This finding was consistent with retrospective studies of adults who had experienced child abuse that showed that psychological and physical health problems co‐occurred into adulthood 3,4 . Early identification and treatment of trauma symptoms may help to reduce the daily health burden of abused adolescents, because such symptoms may already contribute to the development of physical health complaints at a young age 23 . In fact, treating trauma symptoms has been shown to be beneficial for treating physical health complaints in adults 24 …”
Section: Discussionsupporting
confidence: 81%
“…3,4 Early identification and treatment of trauma symptoms may help to reduce the daily health burden of abused adolescents, because such symptoms may already contribute to the development of physical health complaints at a young age. 23 In fact, treating trauma symptoms has been shown to be beneficial for treating physical health complaints in adults. 24…”
Section: P-valuementioning
confidence: 99%
“…There is strong empirical evidence of the association between posttraumatic stress disorder (PTSD) symptoms (reexperiencing, avoidance, and hyperarousal) especially following nondevelopmental trauma such as war and terrorist attack, and SS, in particular chronic pain as the most commonly studied SS (e.g., Bugge et al, 2017; Otis et al, 2003; Wachen et al, 2013). However, still more attention needs to be devoted to unveiling the underlying psychological mechanisms of the association between childhood adversity and SS (McFarlane, 2010; Rueness et al, 2019).…”
Section: Somatic Symptoms Following Early Life Adversitymentioning
confidence: 99%
“…In the current study, we aim to extend scarce previous work that explored PTSD as an underlying mechanism of the complex relationship between exposure to childhood trauma and SS in adulthood (Rueness et al, 2019), using a large heterogeneous sample of Slovene adults. We examine a mediating role of disturbances in self-organization (DSO), consisting of affective dysregulation, negative self-concept, and disturbances in relationships.…”
Section: Somatic Symptoms Following Early Life Adversitymentioning
confidence: 99%
“…Psychological trauma persists through years as posttraumatic stress reactions (PTSR). The recent case indicated that PTSR may be an important mediator in the relationship between child abuse and future physical health complaints [11].…”
mentioning
confidence: 99%